2023
DOI: 10.1177/17562848231170944
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and celiac disease: a review

Abstract: The aim of this review is to broadly cover how the COVID-19 pandemic has affected individuals with celiac disease, including perceived risk, risk of contraction or severe infection, considerations regarding vaccination, access to gluten-free food during the pandemic, and possible long-term changes to the practice of celiac disease management spurred by the pandemic. While initially there was increased perceived risk about COVID-19 in the celiac disease population, studies have found that individuals with celia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Researchers have worked to determine whether CD patients are more likely to experience severe COVID-19 outcomes during the pandemic. Undoubtedly, the pandemic has altered how CD is managed; for example, lockdowns have necessitated the use of new technologies to provide medical care during this time [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have worked to determine whether CD patients are more likely to experience severe COVID-19 outcomes during the pandemic. Undoubtedly, the pandemic has altered how CD is managed; for example, lockdowns have necessitated the use of new technologies to provide medical care during this time [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the experience gained from the COVID-19 pandemic is likely to support pre-COVID-19 evidence regarding the efficacy and good performance of telemedicine and encourage its wider integration into routine clinical practice in general, and in CD patients in particular [ 52 , 54 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the effect of the SARS-CoV-2 vaccine in patients with celiac disease [ 14 ]. Studies from Norway and Italy showed that patients with CD had very good antibody response to vaccination that was comparable to healthy controls [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%